Oral Health in Women with a History of High Gestational Diabetes Risk - Hanna Poulsen; Jukka H. Meurman; Hannu Kautiainen; Anna Maria Heikkinen; Emilia Huvinen; Saila Koivusalo; Johan G. Eriksson (MDPI AG, 2019)
We studied oral health in 115 women with and without a history of gestational diabetes (GDM), expecting poorer oral health in the GDM group. Full-mouth examinations were performed 5 years postpartum and the number of teeth, total dental index (TDI) and decayed, missing, filled teeth (DMFT) index were calculated. Bleeding on probing (BOP), probing depth (PD), visible plaque index (VPI), and clinical attachment level (CAL) were recorded. The periodontal inflammatory burden index (PIBI) was calculated. Panoramic radiographs were taken and signs of infections recorded. Oral health habits, symptoms and participants’ own opinion of oral health were recorded with questionnaires. At the time of examination, 45% of the women had a history of GDM in the index pregnancy. Mild periodontitis (62%) and bleeding on probing (46%) were common. VPI (13% and 17%, p = 0.009) and PIBI (13.1 and 17.5, p = 0.041) were lower among women with a history of GDM compared with those with no history of GDM. There was no difference between groups in DMFT scores. All women reported good subjective oral health. Thus, contrary to our hypothesis, women with a history of GDM showed better oral health parameters than women without a history of GDM.